Research of the Similarity Experiment Mechanism of Face Gear Transmission System Under High Energy Flow Density - Wang Yanzhong; Tang Wen; Liu Yang; Chen Yanyan; Liu Yuanpeng (Jixie chuandong)
The test of face gear transmission under the high- speed and heavy- load requires high performance test equipment. In order to simplify the experiment condition and reduce test cost,the similarity theory of the tooth root bending stress and vibration acceleration is obtained based on the dimensional analysis theorem. The tooth root bending stress and vibration acceleration of face gear under high- speed and heavy- load conditions are measured by the experiment. The bending stress and vibration acceleration of face gear under high- speed and heavy- load conditions are estimated by using the analogical relationship between the face gear prototype and the similarity model establishing with similarity criterion. The prediction of strength and dynamic performance of high- speed and heavy- load face gear under the is realized.